A Lens for Transfer: A History of the Theoretical Frameworks and Conceptual Models Applied to the Study of Transfer Students. (May 2022) - Brinkley-Etzkorn, Karen; Cherry, Leigh
This literature-based study traces the emergence and application of theoretical frameworks and conceptual models applied to the study of higher education transfer students and practices. From the application of early theories in economics and anthropology dating back to the 18th century, to the development of transfer-specific frameworks as recently as 2016, this article reviews primary and secondary sources that apply the theoretical models that researchers have used to understand the complexities of this expanding area of study. Following a chronological approach, the researchers propose six distinct phases of research that have informed this topic. The article concludes with a discussion of the findings and important implications for both research and practice.